BRIDGING EVIDENCE AND PRACTICE: RECOMMENDED PHYSICAL ACTIVITY TYPES FOR OLDER ADULTS WITH HYPERTENSION - Nurma Afiani; Neni Fidya Santi; Kurniawan Erman Wicaksono; Yuli Wahyuni; Sri Haryuni; Novita Ana Anggraini; Abdurahman Wahid (Universitas Kadiri, 2026)
It is evident that physical activity has a significant impact on blood pressure levels in older adults diagnosed with hypertension. However, the type of physical activity among older adults with hypertension remains insufficiently studied. The objective of the present study was to investigate the proposed type of physical activity for older adults suffering from hypertension. The present study was a review, 1280 publications were identified through database searches conducted using ScienceDirect, PubMed, Google Scholar, EBSCO, and Springer Link. PRISMA guidelines were used to report this review. Ten articles met the inclusion criteria, including studies evaluating the effects of physical activity or exercise training on blood pressure; research involving participants diagnosed with hypertension; research reporting findings pertaining to blood pressure; investigations employing an experimental design, written in English, published between 2019-2024. The findings demonstrated that a combination of exercises (aerobic, resistance, and stretching exercises) yielded superior outcomes in comparison to other forms of physical activity in older adults. The findings of this study indicate that resistance training should be performed prior to aerobic exercise in order to achieve optimal results.